VALIDITAS PERANGKAT PEMBELAJARAN BERBASIS MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING CHIPS PADA MATERI SISTEM PENCERNAAN MANUSIA - Mardin, Herinda; Adam, Rosdiana; Solang, Margaretha (Universitas Cokroaminoto Palopo, 2025)
The research is a development research that aims to describe the validity of learning devices based on cooperative learning models of talking chips type on human digestive system material. The method used ini this research is research and development (R & D) modified from Sugiyono (2018). The data collection technique uses a validity sheet. The products developed are teaching modules, teaching materials, LKPD, and question items on the material of the human digestive system. The assessment results show that the learning tools that have been developed meet the criteria with very valid quality. The results of the validation of teaching modules by both expert validators obtained percentage scores ranging from 84-100%, for teaching materials obtained percentage scores ranging from 86-100%, for LKPD obtained percentage scores ranging from 80-100%, and for question items obtained scores ranging from 80-100%. Based on the results of the study, it can be concluded that the learning device based on the cooperative learning model of talking chips type on the material of the human digestive system meets the criteria very valid and can be used for high school students